INNOVATION OF MOTOR VEHICLE TAX SERVICES THROUGH SIGNAL APP (NATIONAL DIGITAL SAMSAT) AT UPTD BALARAJA SAMSAT OFFICE TANGERANG DISTRICT - Devaranti, Shivanka; Murodi, H. Ahmad; Machrunnisa, Machrunnisa (Jurnal Administrasi Negara, 2023)
Citizens who have been officially recognized by legislation as taxpayers are morally and legally bound to fulfill their duty of paying taxes as stipulated in Law No. 28 of 2007, which pertains to general provisions and tax procedures. Tangerang District local governments continue to encounter certain challenges, including the considerable distance between residents' homes and the SAMSAT Office, as well as the accumulation of queues that contribute to a lack of motivation in tax payment. The Balaraja Samsat Office and Tangerang Regency BAPENDA have introduced a new method called Electronic Samsat, which involves utilizing the SIGNAL APP (National Digital Samsat) program developed by the National Police Traffic Corps (KORLANTAS). This initiative is a visionary innovation that is governed by a cooperative agreement with relevant stakeholders and has been implemented in the Banten province since 2021. The SIGNAL application facilitates online car tax payments, allowing users to conveniently make payments through bank transfers or at the nearby minimarket. This research aims to assess the level of innovation in electronic-based motor vehicle tax services using the SIGNAL application at the UPTD of the Balaraja Samsat Office, located in Tangerang Regency. The employed research methodology is qualitative, employing data collection approaches such as interviews, observations, and document reviews. The research findings indicate that the implementation of the SIGNAL (National Digital Samsat) application for motor vehicle tax payment services at the UPTD of the Balaraja Samsat Office in Tangerang Regency has proven to be successful and efficient in facilitating tax payments for individuals. The SIGNAL application enables motor vehicle tax payments to be conveniently made at any location and time, without causing disruptions to community activities.